Drip, drip, drip. (19th March 2013) - Coomer, R.
Summary A unique complication to castration is published in the preceding Case Report in this issue, whereby a 2‐year‐old Thoroughbred racehorse gelding suffered chronic haemoperitoneum weeks after standing castration. The causes and treatment of post castration haemorrhage are reviewed along with haemoperitoneum and the use of laparoscopy. Supplementary explanations are discussed.